Penyuluhan Budidaya Tanaman Obat Tradisional secara Baik dan Benar di Desa Peniron Kecamatan Pejagon Kabupaten Kebumen - Dewi, Fera Listya Sandra; Barokah, Umi; Fatmawati, Nurlaila; Anjariyanto; K, Lisna; Rozaq, Miftakhur; Wahyu, Tri; Silvia, Galuh Iga; Ma’wah, Nuril (Kadiri University, 2023)
Peniron Village is one of the villages in Pejagoan District, Kebumen Regency, where most of the people work as farmers. The survey results and observations in the field found that ginger, greater and lesser galangal, cardamom, curcuma, turmeric, lemon grass, betel leaf, moringa leaves, gotu kola or centella, papaya leaves, cogon grass, lime, bitter bean, pandan leaf, and tamarind were planted on house yard, garden, and mountain areas. In carrying out the process of cultivating medicinal plants, it was found that there were several obstacles experienced by farmers. In order to raise awareness of proper cultivating techniques of these traditional medicinal plants, the PPK Team for Ormawa Himagrotek UMNU Kebumen conducted counseling with the theme